Uchybienia metodologiczne w badaniach ilościowych w językoznawstwie stosowanym - Rysiewicz, Jacek (Neofilolog, 2019)
For quantitative research to be a reliable source of primary-data in second language acquisition (SLA), methodological rigour in positing and testing hypotheses about the nature of factors at play in foreign/second language learning is of paramount importance. Invalid and unreliable tools, irrelevant research questions and/or hypotheses, faulty research designs, and incorrectly used tools of data analysis all lead to erratic and undependable interpretations of the findings. The article is an attempt at a critical appraisal of selected aspects of quantitative research done in Poland over the last two or three years in the area of L2/FL language acquisition/learning. The reports have either been presented at conferences, published in professional journals or carried out in the course of MA and/or PhD dissertations.